Psychological Distress, Disorder Severity, and Perception of Positive Contributions in Couples Raising Individuals With Autism - García-López, Cristina; Recio, Patricia; Pozo, Pilar; Sarriá, Encarnación (Frontiers in Psychology, 2021)
Parents’ perception of the positive contributions associated with raising children with autism is considered to be a protective factor in the process of psychological adaptation. Thus, it is essential to unveil what factors are related to this perception. We explore how parents’ psychological distress (parental stress and anxiety) predicts the perception of positive contributions in fathers and mothers who raise individuals with different levels of autism severity. The sample comprises 135 couples (270 fathers and mothers) parenting individuals diagnosed with autism aged 3–38 years. Participants completed different self-report questionnaires, including measures of parental stress, anxiety, and positive contributions. To estimate the actor–partner interdependence model, data were analyzed using structural equation modeling to explore transactional effects between fathers’ and mothers’ psychological distress and their perceptions of positive contributions associated with autism. Two separate multigroup models were tested, respectively analyzing parental stress and anxiety. Each multigroup model considers two levels of disorder severity. The findings revealed that actor and partner effects of stress and anxiety were important predictors of the perception of positive contributions in both disorder severity groups. We conclude that it is necessary to develop family support programs that focus on controlling fathers’ and mothers’ stress and anxiety symptoms, as these mental states negatively impact the ability to perceive positive contributions.